What Are The Specific Risk Factors Associated With Febrile Seizures In Children Under 5 Years Old In Urban Pediatric Populations ? : A Comprehensive Systematic Review - Mega Reliska; H. Mustarim (International Medical Journal Corp. Ltd, 2025)
Introduction: Febrile seizures (FS) are the most common seizure type in children under five years, especially in urban pediatric populations. These seizures occur with fever without intracranial infection and pose significant clinical challenges due to their acute onset and recurrence risk. Understanding FS risk factors is essential for early identification and prevention. Methods: A systematic review following PRISMA 2020 guidelines was conducted, including 40 studies published since 2015. Studies focused on children aged 0-5 years in urban settings, examining demographic, clinical, genetic, and environmental risk factors for FS. Data extraction covered study design, population characteristics, risk factors, outcomes, and interventions. Boolean MeSH keywords related to pediatric populations, feeding methods, treatments, and FS outcomes guided database searches. Results: Younger age (6-60 months) and family history of febrile seizures showed strong and moderate-to-strong associations with FS risk, respectively. Iron deficiency anemia was prevalent in 38% of FS cases and strongly correlated with seizure occurrence. Other moderate risk factors included low serum zinc and calcium, infections such as HHV-6, and genetic mutations (notably SCN1A). Formula feeding was linked to higher FS occurrence, while exclusive breastfeeding showed a protective effect. Prophylactic treatments like diazepam and sodium valproate reduced recurrence, though safety profiles varied. Nursing and parental education improved symptom management and anxiety. Discussion: FS etiology is multifactorial, involving demographic, clinical, genetic, and environmental factors that often interact, compounding risk. Age-specific strategies—such as genetic screening in infants and iron supplementation in toddlers—are recommended. Urban environmental factors and healthcare disparities further influence FS risk and management. Conclusion: Febrile seizures in urban children under five result from complex, interacting risk factors. Prevention and management require integrated, age-tailored approaches including nutritional support, infection control, prophylactic medication, breastfeeding promotion, and education. Continued research and guideline adherence are vital to improve outcomes.